ROBUST THREE PHASE DYNAMIC TRI-LEVEL H-INVERTER SCHEME - Samia Ali (Journal of Engineering Research - Egypt, 2020)
This paper presents a robust three phase multi-level inverter topology controlled by a programmed micro-controller switching circuit. The inverter consists of three H-type bridges, each bridge comprises four (4) solid state switches. The inverter feeds from a DC battery source or a PV-Fuel Cell-Battery or combination hybrid source. The on/off switching pattern is regulated by the micro-triggering circuit controller. The proposed multilevel inverter improves waveform output quality, lower total harmonics distortion (THD) than the two level one and less electromagnetic interference (EMI). The results show that the inverter output is near to sinusoidal waveform and give the same frequency of the network also the designed inverter improves the power quality and decrease the produced harmonics than the traditional one.